Impact of the COVID-19 Pandemic on traffic performance in Kupang City - Amy Wadu; Mateus R Sodanango; Obed Nenobais (P3M- Politeknik Negeri Kupang, 2022)
Relationship between transportation and people can also be seen when transportation is affected by major changes in society, such as the COVID-19 pandemic. Kupang City found its first case on April 9, 2020, the government has also implemented social restrictions during the pandemic. Therefore measuring traffic performance is very important for government agencies managing traffic and individuals planning trips, especially when special events occur. The purpose of this study was to obtain a model of changes in traffic movement in Kupang City. The results showed that the social restrictions imposed by the Kupang city government only had an impact on roads with educational facilities, while for others there were no significant changes. Meanwhile, for 2022, which is an endemic period or after the COVID-19 pandemic is over, traffic flows on all roads tend to increase and even exceed traffic flows in 2019 which was the period before the pandemic occurred